Advancing Development: The Impact of Geoscience Education in Nigeria’s Rural Coastal Areas of the Niger Delta Region - Chijioke, Nwachukwu Martin; Omeje, Edwin Ogechukwu; Ojukwu, Njideka-Nwawih Charlotte; Benedicta, C. Ozobialu (The Asian Review of Civil Engineering, 2023)
The Niger Delta region of Nigeria is a significant ecological and environmental zone that is classified as a rural coastal area. The development of this region is critical to Nigeria’s socio-economic growth. One of the key factors that have been identified to have a significant impact on the development of this region is geosciences education. Geoscience education helps to develop a better understanding of the natural environment, including the processes that have shaped it and the various resources available to it. This abstract presents an analysis of the impact of geoscience education in the rural coastal areas of the Niger Delta region of Nigeria. A review of existing literature on geosciences education and its impact on the development of rural coastal areas was conducted. The results show that geoscience education has significant potential in the development of the Niger Delta region of Nigeria. The research also indicates that geoscience education enhances awareness of the environmental challenges facing the region, engenders better adaptation to climate change, and underscores the importance of natural resources. Furthermore, geoscience education improves the competitiveness of the rural coastal area residents in the area of agriculture, fisheries, mining, and tourism. Therefore, it is recommended that geoscience education should be included in the curriculum of primary and secondary schools in the rural coastal areas of the Niger Delta region of Nigeria. As well as providing more opportunities for tertiary education and training in relevant geoscience subjects. Furthermore, the importance of these subjects should be widely publicized among community leaders, stakeholders, and residents to ensure they understand the positive impact on education and their development.
Keywords: openalex:import